Technical and economic analysis of a specific spruce wood material drying process - Terziev Angel; Ivanov Martin; Vassilev Momchil; Stankov Borislav (E3S Web of Conferences)
The presented work reveals the technical and economic analysis of a spruce wood material drying process, for a specific installation. The analysis is made of the drying process of spruce timber, where the amount of initial moisture content is 60% and the equilibrium moisture content is 12%. The baseline technological process is considered for the existing installation with a wood burning boiler, used for heat supply source. Three different heat source options were further suggested and analysed, for the wood drying process optimization: implementation of natural gas boiler, electric boiler and high temperature heat pump installation. The calculations for each of them were performed at a heat output of 100 kW and a drying temperature regime of 90/75°C. The results show that only the annual energy costs of the option with a heat pump system are lower than the base case, with the cash savings amounting to USD 4,884/year, payback period of 9.47 years and 99.93 t/year CO2 emissions. The specific energy consumption in this optimal suggested case is 0.139 kWh/kg.